Model of Punishment in an Effort to Form Discipline of Santri at the Tahfiz Putra Darul Qur’an Islamic Boarding School, Mojokerto City - Lulut Julianto; Purwanto (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to determine the types of punishment, the application of punishment, and the discipline of students after being given punishment. It is hoped that the results of this research can contribute to this institution in the formation of Santri discipline. This research was aimed at student students, Tahfiz Putra Darul Quran Islamic Boarding School, Mojokerto City. This research is qualitative research, taking the background of the Tahfiz Putra Darul Quran Islamic Boarding School, Mojokerto City. Data collection was carried out using observation methods, in-depth interviews and documentation. Data analysis uses qualitative descriptive methods and inductive thinking patterns. The aim is to analyze data obtained from field objects, then connect it with relevant theories. The results of the research show: 1) the various punishments applied at the Tahfiz Putra Darul Quran Islamic Boarding School, Mojokerto City, namely repressive punishment because the punishment is imposed after the child commits a violation, are normative because the punishment applied has the aim of improving the morals of the Santri, is logical where the punishment given is a logical consequence of bad actions, and is mental punishment because the punishment given is not directly related to the physical, and is educational because it is in accordance with the theory of improvement given so as not to repeat the violation and correct what has been done. 2) application of punishment at Madrasah Diniyah. The application of this type of punishment shows the formation of the Santri's attitude in carrying out the rules and regulations that have been implemented. 3) Discipline of Santri becomes better with the implementation of punishment as a sanction for violations committed by Santri.